Os reflexos da pandemia Covid 19 nos indicadores de controle orçamentários, financeiros e sociais no município de Alegrete/RS - Machado, Patrício Silveira (2022)
The present study is directly related to the reflexes of the COVID-19 pandemic on budgetary, financial and social control indicators in the management of the municipality of Alegrete/RS. Such indicators make it possible to compare situations between municipalities or between different periods within the same municipality. The period covered by the work were the exercises of 2016 (without a pandemic) and 2020 (with a pandemic), which represent, consequently, the last period of the 2013/2016 and 2017/2020 administrations of the municipality under study, having as a north of this research, to seek answers to the following question: how did the budgetary, financial and social control indicators of the municipality of Alegrete/RS behave during the period marked by the Covid 19 pandemic? Its main objective was to highlight the variation of budgetary, financial and social control indicators in the Municipality of Alegrete/RS during the period characterized by the Covid 19 Pandemic. The study is characterized as an investigation based on descriptive research, and under a qualitative approach. The budget control indicators showed a similar behavior in the 2016 and 2020 fiscal years; the financial control indicators indicated a surplus flow of financial resources in 2020, while in 2016 it was in deficit. As for the social indicators that contribute to the assessment of the population's living conditions and well-being, such as education, health, security, employment and income, the year 2020 showed a drop in the enrollment rate, a reduction in per capita education spending, low infant birth rate and negative population growth, decrease in the stock of jobs and worsening crime indicators. To further contribute to the assessment of public finance conditions in the Municipality of Alegrete, the Brown Model (1993), CICA Model (1997), Chaney et al. (2002) and the Model by Wang et al. (2007). With the exception of the Brown Model (1993), which presented an inconclusive result, the other models showed that the condition of the municipality's public finances showed a setback in the 2020 year in relation to the year 2016. Thus, it is concluded that the behavior of the indicators of the Municipality of Alegrete/RS in 2020 (pandemic year) compared to 2016 (non-pandemic year), showed deterioration of the variables that contribute to the assessment of the living conditions and well-being of the population. As for the budget control indicators, in the respective years (2016 and 2020), they presented a proper financial programming of the budget, demonstrating a situation of budgetary balance in the two years. Financial control indicators show improvement in 2020 due to the increase in revenue that generated a surplus financial flow. And finally, the assessment of the financial health conditions of the municipality, through the Assessment Models of CICA (1997), Chaney et al (2002) and Wang et al (2007), showed fragility in the 2020 fiscal year in relation to the exercise of 2016, mainly due to the increase in its long-term obligations.